Prostate biopsy histopathologic features correlate with a commercial gene expression assay's reclassification of patient NCCN risk category. Issue 16 (18th September 2020) - Greenland, Nancy Y.; Cowan, Janet E.; Chan, Emily; Carroll, Peter R.; Stohr, Bradley A.; Simko, Jeffry P.
Abstract: Background: For biopsies with Gleason 3 + 3 = 6 or 3 + 4 = 7 prostate cancer, the Genomic Prostate Score (GPS; OncotypeDx) is designed to predict severe pathology at prostatectomy, and, in some cases, recommends reclassification of the National Comprehensive Cancer Network (NCCN) risk category. We hypothesized that certain histopathologic features that were not considered in the original design of the assay actually would be associated with the NCCN risk category change indicated by GPS testing. Methods: For patients with recommended NCCN risk category change, the biopsy cores used for GPS were re‐reviewed for stromal reaction, chronic inflammation, and tumor nuclear polarization. Results: Of 520 patients from May 2011 to December 2018, GPS testing suggested NCCN risk reclassification in 131 (25%); 127 of these slides were available. Of these, the NCCN risk category increased from intermediate to high in 8, low to intermediate in 15, very low to low in 1, and decreased from intermediate to low in 32, and low to very low in 71. Biopsies with NCCN risk increase were associated with moderate or severe stromal reaction ( p  < .001) and chronic inflammation ( p  < .001); biopsies with NCCN risk decrease were associated with absence of these features. In Gleason 3 + 3 = 6 cases ( n  = 93), presence of nuclear polarization was associated with NCCN risk decrease and its absence with increase ( p  < .001). Conclusions: Moderate or severe stromal reaction, chronic inflammation, and lack of nuclear polarization in Gleason score 3 + 3 = 6 tumors were each associated with an increase in NCCN risk category indicated by GPS and vice versa. Our results suggest that GPS captures histologic features associated with aggressiveness that are not routinely assessed in standard histopathologic assessments, and that consideration of such histologic features may improve upon current tumor grading approaches.